Integrative evidence-based athlete assessment and intervention: A field-tested and validated protocol - Carlstedt, R. A. (The Journal of the American Board of Sport Psychology, 2007)
This article presents a comprehensive evidence-based and field-tested athlete assessment and intervention protocol that has been validated over the last ten years. It is based on an integrative individual-differences model of peak performance, one that stresses ecological validity, real-time monitoring, on-the-playing-field individualized interventions (during practice and competition) and testing mental training methods for efficacy. It stands in stark contrast to conventional practices that are marked by loosely and arbitrarily administered eclectic, hybrid and poorly controlled and documented athlete evaluation and mental training methods. The protocol was designed to better illuminate complex mind-body-performance processes through the use of advanced and sophisticated instrumentation, testing paradigms, methodologies and interventions that have a high degree of validity and reliability. It advances a step-by-step hierarchical evidence-based approach that is predicated on the comprehensive assessment of athlete neuropsychophysiological responses prior to, during and after practice and competition and in the context of mental training. It will be shown how this approach to science-based applied sport psychology can be used to gain unprecedented insight into the mental game, better predict psychological tendencies, intervene more effectively and utilize databases of mind-body measures to empirically quantify the player selection, development and mental preparation process.